2014
DOI: 10.5423/ppj.nt.08.2014.0073
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Selective Medium for the Fungal Pathogen Cylindrocarpon destructans Using Radicicol

Abstract: The soil-borne ascomycete fungus Cylindrocarpon destructans causes ginseng root rot disease and produces various secondary metabolites such as brefeldin A and radicicol. The slow growth of this fungus compared with other plant pathogenic and saprophytic fungi in soil disturbs isolation of this fungus from soil and infected ginseng. In this study, we developed a selective medium for C. destructans using radicicol produced by this fungus. Supplementing 50 mg/L of radicicol to medium inhibited the mycelia growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…The soil-borne pathogenic fungus Cylindrocarpon destructans (teleomorph: Nectria/Neonectria radicicola) can cause a primary root rot disease in ginseng (Panax ginseng and P. quinquefolius) and reduce the root yield of ginseng resulting in great economic losses (Chung 1975;Rahman and Punja 2005;Kang et al 2014). In addition, C. destructans has been reported to lead to replant failure, due to its ability to survive in the soil for more than 10 years after the harvest of ginseng (Kang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The soil-borne pathogenic fungus Cylindrocarpon destructans (teleomorph: Nectria/Neonectria radicicola) can cause a primary root rot disease in ginseng (Panax ginseng and P. quinquefolius) and reduce the root yield of ginseng resulting in great economic losses (Chung 1975;Rahman and Punja 2005;Kang et al 2014). In addition, C. destructans has been reported to lead to replant failure, due to its ability to survive in the soil for more than 10 years after the harvest of ginseng (Kang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pochonins and monocillins have been well-documented in other species of the same taxonomic order as I. mors-panacis, the Hypocreales, such as Pochonia chlamydosporia and Monocillium nordinii (teleomorph Niesslia) and have antimicrobial effects against several organisms [21][22][23]. Antimicrobial RALs may indirectly assist I. mors-panacis and I. robusta in colonizing ginseng roots, by acting against other pathogens inhabiting the same soil environment [11]. This may give root rot pathogens an improved chance of surviving in the soil, and of eventually infecting ginseng.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of metabolites have been previously identified in extracts from Ilyonectria and Neonectria strains isolated from ginseng. These include the antifungal compound radicicol and the antiviral brefeldin A [11]. Radicicol is potently antifungal against several species of pathogenic fungi that inhabit the same environment as ginseng root pathogens [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no studies on the antifungal activity of RAD against Cryptococcus spp., it is well known that this drug has antifungal activity against many fungal pathogens, such as Candida albicans, Paracoccidioides brasiliensis, Aspergillus fumigatus, Fusarium avenaceum and Mucor flavus (Fujita et al, 1999;Nicola et al, 2008;Chen et al, 2011;Kang et al, 2014). These studies have shown that RAD inhibits fungal growth at concentrations ranging from 0.365 to 50 mg ml…”
Section: Discussionmentioning
confidence: 99%